2020
DOI: 10.1128/iai.00530-19
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of msaABCR on sarA -Associated Phenotypes Are Different in Divergent Clinical Isolates of Staphylococcus aureus

Abstract: The staphylococcal accessory regulator (sarA) plays an important role in Staphylococcus aureus infections, including osteomyelitis, and the msaABCR operon has been implicated as an important factor in modulating expression of sarA. Thus, we investigated the contribution of msaABCR to sarA-associated phenotypes in the S. aureus clinical isolates LAC and UAMS-1. Mutation of msaABCR resulted in reduced production of SarA and a reduced capacity to form a biofilm in both strains. Biofilm formation was enhanced in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 53 publications
(72 reference statements)
4
17
0
Order By: Relevance
“…fluorescence was significantly higher in the sarA mutants with all four reporters including the spl::gfp reporter, and this was true in both LAC and UAMS-1 (Rom et al, 2020). This confirms that SarA represses expression of all four of the transcriptional units encoding aureolysin, ScpA, SspA/SspB, and SplA-F, and the results of our binding assays suggest that it does so by directly binding to cis elements associated with all four of the relevant promoter regions.…”
Section: A Csupporting
confidence: 79%
See 2 more Smart Citations
“…fluorescence was significantly higher in the sarA mutants with all four reporters including the spl::gfp reporter, and this was true in both LAC and UAMS-1 (Rom et al, 2020). This confirms that SarA represses expression of all four of the transcriptional units encoding aureolysin, ScpA, SspA/SspB, and SplA-F, and the results of our binding assays suggest that it does so by directly binding to cis elements associated with all four of the relevant promoter regions.…”
Section: A Csupporting
confidence: 79%
“…Changes in the production of extracellular proteases have been correlated with clinically-relevant phenotypes of S. aureus including the accumulation of alpha toxin and protein A, biofilm formation, and virulence in diverse animal models (Beenken et al, 2010, Kolar et al, 2013, Loughran et al, 2014, Mootz et al, 2015, Rom et al, 2017, Rom et al, 2020, Trotonda et al, 2008, Tsang et al, 2008. Indeed, eliminating the production of aureolysin, SspA, SspB, ScpA, and the SplA-F proteases, or increasing the production of these same proteases, has been shown to have a dramatic impact on virulence and the overall S. aureus virulence factor repertoire (Byrum et al, 2018a, Kolar et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, msaABCR whole cell proteomics analysis also showed significant production of SspA, SspB, SspC, Aur, and staphopain A. A study by Rom JS et al, [ 84 ] showed reduced accumulation of alpha toxin (Hla) and extracellular protein A in the msaABCR mutant [ 84 ]. They also showed that deletion of msaABCR leads to the significant decrease in accumulation of extracellular proteins [ 84 ].…”
Section: Discussionmentioning
confidence: 50%
“…Several staphylococcal virulence factors that are cytotoxic to osteoblasts, triggers osteoclastogenesis, and induces bone loss and/or destruction are also affected in the msaABCR mutant (Table 2 ). Several previous studies have linked increased protease production with defective biofilm formation, reduced accumulation of secreted virulence factors, reduced toxicity to osteoblasts and osteoclasts cells in vitro, and reduced virulence and attenuation in OM infection [ 31 , 46 , 51 53 , 73 , 84 ]. Cassat et al 2013 [ 46 ] showed that extracellular-secreted proteases, mainly aureolysin (Aur), significantly reduced the abundance of staphylococcal exoproteomes that are important for host-tissue binding, biofilm formation, invasion of host cells, and the cytolytic factors that trigger cortical bone destruction.…”
Section: Discussionmentioning
confidence: 99%